SCREENING OF POTENTIAL WEEDS GROWN IN OIL-PALM PLANTATION FOR ANIMAL FEEDS AT JAMBI PROVINCE - Tarsono, Tarsono; Hafsah, Hafsah; Kaswari, T (AgriSains, 2016)
Vegetation that grows naturally in certain areas is a reflection of the interaction of various environmental factors and may change at any time. Under oil palm trees, there are several types of vegetation that have the potential to be used as animal feed, but it has not been identified yet. This study aimed to examine the types of vegetation that grows under the oil palm trees, and could potentially be used for animal feed. Observations were conducted on 3 groups of oil palm plantations aged above 10 years which belong to:  i.e. smallholder oil palm, private estates, and state estates company. In each group, it was taken 8 plots so there were 24 plots in total. Parameters observed were the types of plants (i.e. grass, legume, and weed), plant nutrient content (determined by using proximate analysis), microclimate and soil organic matter content (C and N), and soil pH. Collected data were analyzed descriptively, and were followed by a t test.   Results showed that herbages grow in palm-oil plantation in the Ness village are more various than that of in the Arang-arang village.  Ottocloa nodosa and Eulisine indica are two grasses species that might be potential in the Arang-arang village which has a pity soil type, while Leersia hexandra, Paspalum sp., and Ottocloa nodosa are species of grasses which grow in the Ness village which has a yellow-red podsolic soil type.  The existence of Melastoma malabathricum in the Arang-arang village should be considered as this species contains poisonous substances.  Calopogonium sp. and Mimosa sp. are spesies of legumes that could be developed in palm-oil pasture to improve N content of herbages.  Nitrogen or mineral fertilization might be needed to improve soil fertility of different soil types.Key words: oil palm, vegetation, weeds, animal feed, soil